2007
DOI: 10.1158/1535-7163.mct-06-0564
|View full text |Cite
|
Sign up to set email alerts
|

Docetaxel-induced apoptosis in melanoma cells is dependent on activation of caspase-2

Abstract: Taxanes have a broad spectrum of activity against various human cancers, including melanoma. In this study, we have examined the molecular mechanism of docetaxelinduced apoptosis of human melanoma. We report that docetaxel induced varying degrees of apoptosis in a panel of melanoma cell lines but not in normal fibroblasts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
87
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 84 publications
(96 citation statements)
references
References 40 publications
9
87
0
Order By: Relevance
“…A375 cells (NCBI# C136) and human skin fibroblast-like HFFF2 cells (NCBI# C163) were purchased from the National Cell Bank of Iran (NCBI, Tehran). Origin and characteristics of these lines have been reported previously (Zhang et al, 1999;Wua et al, 2005;Mhaidat et al, 2007).…”
Section: Culture and Treatment Of Melanoma Cellssupporting
confidence: 52%
“…A375 cells (NCBI# C136) and human skin fibroblast-like HFFF2 cells (NCBI# C163) were purchased from the National Cell Bank of Iran (NCBI, Tehran). Origin and characteristics of these lines have been reported previously (Zhang et al, 1999;Wua et al, 2005;Mhaidat et al, 2007).…”
Section: Culture and Treatment Of Melanoma Cellssupporting
confidence: 52%
“…In support of this, an independent study has shown that docetaxel-induced apoptosis is dependent on caspase-2 activation (Mhaidat et al, 2007). Paclitaxel (Pacl) is a member of the Taxanes family and has a similar mode of action to docetaxel, in that it functions as a microtubule-stabilizing agent (Mhaidat et al, 2007). In contrast, Vinc acts to depolymerize microtubule filaments, whereas cyto D inhibits polymerization of actin filaments and has been shown to activate p53-dependent death (Bhalla, 2003).…”
Section: Figure 4 Similar Cytoskeletal Changes Induced By Vincristinementioning
confidence: 99%
“…In support of this, an independent study has shown that docetaxel-induced apoptosis is dependent on caspase-2 activation (Mhaidat et al, 2007). Paclitaxel (Pacl) is a member of the Taxanes family and has a similar mode of action to docetaxel, in that it functions as a microtubule-stabilizing agent (Mhaidat et al, 2007).…”
Section: Figure 4 Similar Cytoskeletal Changes Induced By Vincristinementioning
confidence: 99%
See 1 more Smart Citation
“…Somehow, taxanes have been found to be not cell specific with not all concentrations displaying similar effects on microtubules dynamics (Schiff et al, 1979;Schiff and Horwitz, 1980;Jordan et al, 1993;Derry et al, 1995;Jordan et al, 1996;Jordan and Wilson, 1998;Yvon et al, 1999) relating to unsimilar cytotoxic, anti-proliferative and apoptotic effects on various cancer cell lines namely breast, lung, ovary, prostate, hepatic, melanocyte and leukemic (Jordan et al, 1993;Jordan et al, 1996;Ferlini et al, 1998;Nehmé et al, 2001;Geng et al, 2003;Wang et al, 2005;Mahaffey et al, 2007;Mhaidat et al, 2007;Ichite et al, 2009;Kang et al, 2010). Though killing of malignant cells is the main aim for all researchers, scientists, cancer physicians and pharmaceutical companies; however, there are still many hedges and thorns to be overcome in order to attain a successful and irreproachable cancer therapy.…”
Section: Introductionmentioning
confidence: 99%